Historical evolution and future perspectives in the management of radio, film, television and advertising heritage - Marcos Recio, Juan Carlos; de la Cuadra de Colmenares, Elena; Fernández Sande, Manuel (Revista General de Información y Documentación, 2018)
Audiovisual material, including advertising content, constitutes one of the most fragile and vulnerable aspects of our shared cultural heritage. Films, radio and television programmes and advertising spots provide special insight into how societies and cultures evolve. Despite technological advances in data storage that have opened up new opportunities to archive audiovisual material on a massive scale, media heritage management continues to be a complicated and challenging task. Most communications organizations have yet to devise efficient strategies for the conservation and exploitation of their archives. Governments have also been slow to develop coherent, long-term policies on the protection and conservation of audiovisual heritage. This article provides a general overview of audiovisual heritage management today, beginning with a historical review of work in this field before moving on to an analysis of the greatest problems facing archivists charged with conserving audiovisual material today and case studies of professional best practices.
Keywords: Audiovisual heritage; radiophonic heritage; cinematographic heritage; television heritage; adversiting heritage